Membandingkan Efisiensi Bank Syariah Di Indonesia Dan Malaysia Dengan Metode Data Envelopment Analysis (DEA) - Hikmah Maulidiyah; Nisful Laila (Universitas Airlangga, 2016)
This study measured and compared the efficiency of Islamic Bank in Malaysia and Indonesia. This sytudy used a quantitative non-parametric approach by using Data Envelopment Analysis (DEA)VRS assumption, and a statistic tool Mann-Whitney-U-Test. The samples were 6 Islamic Banks in Malaysia and 10 Islamic Bank in Indonesia that comply with the specified sample criteria during 2010-2014.The results of this research showed that Islamic Banks in Indonesia relatively higher than Islamic Bank in Malaysia based on VRS assumption. Source of inefficiency in Islamc banks in Indonesia more due to inefficiency on a scale. While the hypothesis test showed that there are no significant differences of efficiency between Islamic bank in Indonesia and Malaysia with VRS Assumtion .